Macrozoobenthos Community Structure in the Coastal Waters of Marsegu Island, Maluku, Indonesia - Fitry Yunita; Fredy Leiwakabessy; Dominggus Rumahlatu (International Journal of Applied Biology, 2018)
The existence of macrozoobenthos in an ecosystem is closely related to the conditions of the surrounding environment. This research aimed to examine the physical chemical condition of aquatic environment and macrozoobenthos community structure in the coastal waters of Marsergu Island. This research was conducted in July and December 2016 in 3 stations. The data were collected by using sampling technique to measure the environmental factors (temperature, salinity, pH, and dissolved oxygen of seawater) and enumeration of gastropod species with in-situ. The results of this research showed that macrozoobenthos in the coastal waters of Marsegu Island consisted of 2 Phylum, namely Molusca and Echinoderms, that is, gastropod with 18 species, bivalvia with 5 species, and echinoderms with 17 species. Echinoderms was the dominant macrozoobentos with a percentage of 45%, followed by gastropods 42%, and bivalvia 13%. This suggests that echinoderms and gastropods are the main components that make up the macrozoobenthos community structure in the coastal waters of Marsegu Island. The results of the calculation of the diversity index of macrozoobenthos in the three research stations showed the highest score was station 1 as much as 3.56, station 2 as much as 3.52 and the lowest was station 3 as much as 2.07.